1983
DOI: 10.4141/cjas83-027
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Nylon Bag Technique for Determining Apparent Digestibilities of Protein in Feedstuffs for Pigs

Abstract: Sauln, W. C., JoncENseN A method for measuring protein digestibility of small feed samples was developed with growing pigs fitted with a single cannula in the duodenum. Feed was ground through a 0.8-mm mesh screen and 1-g samples were enclosed in 25 x 40-mm monofilament nylon bags (50-pm mesh). Following pre-digestion in vitro to simulate gastric digestion (0.01 N HCI; pepsin I glL 2.5 h), the bags were inserted into the small intestine vra the duodenal cannula. recovered in feces within 48 h. frozen, lyoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
114
0
5

Year Published

1985
1985
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(120 citation statements)
references
References 0 publications
1
114
0
5
Order By: Relevance
“…In the same study it was also found that incubation with a pancreatin solution gave similar results to those obtained with the mobile nylon-bag technique (Sauer et al 1983(Sauer et al , 1989, which can be considered as an intermediate between in vivo and in vitro methods. In fact, many in vitro methods are based on consecutive incubations with pepsin and pancreatin, suggesting that pancreatin contains all the necessary enzymes for solubilizing the potentially digestible nutrients.…”
Section: Enzyme Speclficitysupporting
confidence: 65%
“…In the same study it was also found that incubation with a pancreatin solution gave similar results to those obtained with the mobile nylon-bag technique (Sauer et al 1983(Sauer et al , 1989, which can be considered as an intermediate between in vivo and in vitro methods. In fact, many in vitro methods are based on consecutive incubations with pepsin and pancreatin, suggesting that pancreatin contains all the necessary enzymes for solubilizing the potentially digestible nutrients.…”
Section: Enzyme Speclficitysupporting
confidence: 65%
“…During days 10-14, faecal and urine samples for the mass balance experiments were collected. During days 15 -16, the pigs were surgically fitted with a distal ileal cannula according to previously established procedures (14) . Following a post-surgical recovery period (days [17][18][19][20], the pigs resumed their previous feeding schedule for the duration of the experiment.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…The duodenal cannula was similar to the re-entrant pancreatic cannula descrided by Hee et al (1985). The surgical technique of Sauer et al (1983) was adapted for the insertion of the ileal cannula, whereas the duodenal cannula was inserted using the technique described by Hee et al (1985). The gilts were fasted for a 24 h period and then sedated one hour prior to surgery with a 1 ml intramuscular injection of Atravet (Ayerst Laboratories, Montreal, Quebec, Canada).…”
Section: Animals and Managementmentioning
confidence: 99%
“…The ileal cannula was designed according to Sauer et al (1983) as modified according to de Lange et al (1989). The duodenal cannula was similar to the re-entrant pancreatic cannula descrided by Hee et al (1985).…”
Section: Animals and Managementmentioning
confidence: 99%